Breath analysis - Pennazza, Giorgio; Santonico, Marco (Academic Press, 2019)
Breath Analysis presents state-of-the-art research in this specialized field, also offering guidance on how best to design the technology and conduct analysis. The book primarily focuses on the diagnosis of lung cancer, asthma and Chronic Obstructive Pulmonary Diseases. The reliability, consistency and utility of the results from breath analysis depends on exhaled breath sampling procedures and tools, gas sensor array technology (sensing material and transducer), and finally, medical pertinence and interpretation. The book gives step-by-step procedures and discusses best practice solutions for problems in sample collection, sensor technology, clinical assessment, medical interpretation and data analysis. The book's primary audience would include biomedical engineers and medical doctors, but it is also useful for hospital technicians, hospital and biomedical SME leading figures, and those in PhD level Engineering and Medicine.